Knowledge, Attitude, and Practice of Weaning among Mothers in Najran Region, Saudi Arabia, 2021 - Musalli Ali Al-Gashanin; Eisa Yazeed Ghazwani (Journal of Nutrition and Metabolism)
Background. Weaning is a complex process of a gradual introduction of complementary foods to the infant’s diet. It is recommended that solid food is introduced between 6 and 12 months of age. Weaning is difficult and potentially dangerous time for infants’ growth and mother’s education is an established determinant of its success. Little is known about weaning attitudes or practice among mothers in Najran Region of Saudi Arabia. Method. The study is a cross-sectional questionnaire-based observational investigation using random sampling scheme. We utilized ordinal logistic regression modelling to evaluate the relationship between demographic variables and knowledge level among mothers. Results. The total number included was n = 385 mothers who agreed to take part in the study. Good satisfactory knowledge rate was n = 135, 35.1%. Knowledge was mostly sought from other mothers (n = 102, 26.5%), followed by reliance on their own experience (n = 82, 21.3%). Seeking doctors’ advice was associated with better knowledge levels. Worse adjusted knowledge scores were associated with bottle feeding (OR = 0.5383, p=0.0137), using cerelac preparations (OR = 0.0316, p=0.0092), development of weaning symptoms (OR = 0.5869, p=0.0260), seeking other mothers’ advice (OR = 0.4750, p=0.0226), and feeding babies under 4 times daily (OR = 0.2742, p=0.0008). Mother education did not have significant impact on knowledge scores. Discussion. We confirmed, in this work, that knowledge levels were alarmingly unsatisfactory about weaning among our participants. Women were likely following local customs in terms of their choice of weaning methods even among the well-educated. The association between seeking doctors’ advice and better knowledge should be utilized in future educational interventions. Underfeeding babies of below 4 times daily was correlated substantially with poorer knowledge score. This could be viewed as reverse causality, as clearly more knowledgeable mothers are expected to stick to optimum feeding frequency. Recommendations. Communication channels between physicians and mothers need to be opened and widened through focused educational programmes. Poor knowledge is clearly associated with infant underfeeding and difficulties in recognizing weaning symptoms. Such points need to be emphasized in design of health education packages to nursing mothers. Research on knowledge about weaning should focus on its association with traditional weaning methods and bottle feeding.